Unlocking Small Business Growth Strategies for Success in Indonesia: Mengungkap Strategi Pertumbuhan Usaha Kecil untuk Sukses di Indonesia - Rochani, Oktavia Siti; Pradhana, Muhammad Farid Fathul Huda; Ramadhin S, Ede; Zahrina A, Nilamsari; Haris, Abdul; Rahmawati , Imelda Dian (Indonesian Journal of Law and Economics Review, 2024)
This study analyzes the development strategy of "Kenangan Fried Chicken," a small business in Sidoarjo Regency. Using qualitative research and a phenomenological approach, data were gathered through interviews, observations, and SWOT analysis. The findings highlight that product quality, marketing, and competition are crucial for growth. Strengths include a strategic location, while weaknesses involve limited capital. High community enthusiasm presents opportunities, but competition poses a threat. Recommended strategies include improving product quality, diversifying the menu, and enhancing marketing efforts to boost business competitiveness and sustainability. Highlights: Strategic Location: Prime spot in a residential area near main road. Marketing Importance: Essential for growth and overcoming competition. Capital Constraints: Major weakness hindering business sustainability. Keywords: small business development, Kenangan Fried Chicken, qualitative research, SWOT analysis, marketing strategy